Cetylpyridinium Bromide-Modified Montmorillonite as Filler in Low Density Polyethylene Nanocomposite Films - Rodriguez-Mercado, F; Bruna-Bugueno, J; Galotto-Lopez, M; Muñoz-Shuguli, C (Elsevier Ltd, 2019)
The development of clay polymer nanocomposites has been presented as an interesting alternative for design of new active food packaging materials. In this work, low density polyethylene (LDPE) nanocomposites with cetylpyridinium bromide (CPB) – modified montmorillonite (Mt) were developed. In a first stage, Mt. was modified with different CPB proportions based on cation exchange capacity (1:1 and 2:1), resulting in two different organoclays. These modified clays were hydrophobic and presented a good thermal stability that favored their capacity for extrusion to develop LDPE nanocomposites. Based on the incorporated organoclay, nanocomposite films showed important changes in morphology, and differences in mechanical properties, crystallinity, and gas permeability in comparison to polyethylene. All nanocomposites showed greater opacity than LDPE, however, their color changes did not exceed the visual perception limit. Finally, electrical conductivity (EC) measurements showed that CPB was able to migrate from the nanocomposite films to an aqueous food simulant. This behavior was dependent on the availably of free CPB in the matrix, its disposition in the organoclay and the organoclay distribution into the polymer matrix. These results highlight the migration of the surfactant from LDPE nanocomposites with Mt./CPB organoclays, making montmorillonite a potential surfactant carrier that increases compatibility and function in polymers allowing the generation of novel materials that could be used in the design of food packaging. © 2018 Elsevier B.V.
Keywords: Montmorillonite; Cetylpyridinium bromide; Polyethylene; Nanocomposites; Migration